2023
DOI: 10.56397/jrssh.2023.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Market and Conservation Education Influences on Global Zoo and Aquarium Animal Collections

Abstract: There is evidence to suggest that visitors to zoological collections prefer to see large, active mammals. To attract visitors, zoos and aquariums might be tempted to select for mammal species in their collection plans to maintain visitor interest. However, collections also play a role in endangered species breeding, many of which are not mammals. Using International Zoo Yearbook data, we explored the number of species of mammals, birds, reptiles, amphibians, fish and invertebrates housed in collections across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Studies have shown how vital zoos are for recognizing and treating health problems in reptiles, such as the part played by infections like Pseudomonas aeruginosa in crocodile lizard skin ulcer illnesses, and for providing control measures that aid in conservation efforts [23]. Zoos also use their housed frogs to educate the public about conservation issues and to rally support for the preservation of these species [24].…”
Section: )mentioning
confidence: 99%
“…Studies have shown how vital zoos are for recognizing and treating health problems in reptiles, such as the part played by infections like Pseudomonas aeruginosa in crocodile lizard skin ulcer illnesses, and for providing control measures that aid in conservation efforts [23]. Zoos also use their housed frogs to educate the public about conservation issues and to rally support for the preservation of these species [24].…”
Section: )mentioning
confidence: 99%